The theory and applications of controlled release principles - Rathbone, Michael J. (Henry Stewart Talks, 2018)
Definition of a controlled release (CR) product, Introduction to controlled release drug delivery, Advantages and disadvantages of formulating a drug into a CR product, Formulation approaches and mechanisms of drug release, Applications (examples) of controlled release products in the human field, Applications (examples) of controlled release products in the veterinary field